Pengembangan Media Pembelajaran E-Modul Interaktif Materi Pola Gerak Dasar - Haqiqi, M. Wildan; Sari, Zihan Novita (Populer: Jurnal Penelitian Mahasiswa, 2024)
Based on the results of the needs analysis of PJOK teachers in class IV SDN Kanigoro 04, teachers use LKS learning media or manual teaching books. LKS or manual textbooks are less interesting because the LKS used is not colorful so the teacher feels that the current media is not enough to support interactive learning. The difficulty that teachers face when making interactive media is that it takes a long time. The purpose of this research is to develop and test interactive e-module learning media on basic movement patterns and create a new learning atmosphere. Researchers used a Research and Development approach with the ADDIE development research model (Analyze, Design, Development, Implementation, Evaluation). The results of media expert validation got an average result of 91.87% which was categorized as very valid, material expert validation got an average result of 95.83% which was categorized as very valid. Small group trials to students obtained an average result of 91.49% categorized as very feasible. Large group trials to students obtained an average result of 90.28% categorized as very feasible. This shows that the use of interactive e-module learning media on basic movement patterns is very feasible to use in learning.